Vernacular English : Reading the Anglophone in Postcolonial India - Saxena, Akshya, 1986- (Book collections on Project MUSE., 2022)
"After India's Partition and independence in 1947, "cleansing" Hindi by removing Urdu words was part of the nation's effort to disavow Islamic influence and to forge an exclusively Hindu "Indian" identity. Sanskritized Hindi was anointed the official language of India in 1950, a move protested by non-Hindi-speaking people; in 1963, lawmakers responded to these protests by making English an associate official language. Itself a language steeped in a history of colonial violence, English nevertheless was chosen to mend the gaps created by the imposition of Hindi and to uphold the ideal of democracy. This book considers English as part of the multilingual local milieu of India (a country where more than twenty languages are spoken) not as a colonial language imposed from without. Through a close study of English in India, from the language policies under British rule to the present day, Akshya Saxena argues that low castes and minority ethnic groups-those oppressed by or denied access to English-have routinely and effectively used the language to make political demands on the state. The book examines the ways that Indians use English in literary, spoken, and visual media, from novels to films to global protest movements, to express and shape their experience within the Indian state"--